Exploring Potential of Tree Diversity Using Ecoprint Techniques in Tahura Bunder, Gunungkidul, Yogyakarta - Yuslinawari Yuslinawari; Ni Putu Rani Nadya Swari; Erni Sulistyowati (TECHNO: JURNAL PENELITIAN, 2026)
Forest products that currently need to be developed are studies of diversity and opportunities for increasing their economic value. The value developed is to reduce the rate of forest destruction. This study aims to determine the potential of ecoprint from the diversity of plant species in the Traditional Block of the Bunder Grand Forest Park, Gunungkidul, D. I. Yogyakarta. Ecoprint as an eco-friendly fabric dyeing technique. The research method is observation, trial and interview. Observation is carried out to identify diversity. Trial with ecoprint making processing and interviews for result assessment. The determination of the number of samples used is Purposive Sampling of 30 species for observation. Ecoprint making using the pounding method ecoprint technique. The results were assessed through a Likert Scale-based questionnaire by 93 respondents consisting of students and lecturers of the Faculty of Forestry Instiper, as well as Tahura managers. The result showed that there The application of the ecoprint pounding technique, not only serves as a method for identifying tree diversity but also offers an opportunity to increase the economic value of non-timber forest products (NWFP) while supporting environmental conservation. Nine species in three clusters received the highest or most preferred ratings are  (1) Randu (Ceiba pentandra Gaertn.); (2) Gambiran (Carmona retusa);  (3) Dadap (Erythrina variegata L.) (4) Kesambi (Schleichera oleosa (Lour.); (5) Sapodilla/Sawo Kecik (Manilkara kauki (L.) Dubard); (6) Candlenut (Aleurites moluccana L.); (7)Bungur (Lagerstroemia speciosa); (8) Bendo (Artocarpus elasticus) and (9) Walikukun (Schoutenia ovata Korth.).